Data from: Failure to coordinate management in transboundary populations hinders the achievement of national management goals: the case of wolverines in Scandinavia ... - Gervasi, Vincenzo (Dryad, 2019)
1. Large carnivores are expanding in Europe, and their return is associated with conflicts that often result in policies to regulate their population size through culling. Being wide-ranging species, their populations are often distributed across several jurisdictions, which may vary in the extent to which they use lethal control. This creates the conditions for the establishment of source-sink dynamics across borders, which may frustrate the ability of countries to reach their respective management objectives. 2. To explore the consequences of this issue, we constructed a vec-permutation projection model, applied to the case of wolverines in south-central Scandinavia, shared between Norway (where they are culled) and Sweden (where they are protected). We evaluated the effect of compensatory immigration on wolverine population growth rates, and if the effect was influenced by the distance to the national border. We assessed to what extent compensatory immigration had an influence on the number of removals ... : R-code used to run the 2-patch 2-stage vec-permutation model.Appendix 3.docx ...